Connectivity Index Approach for Evaluating Transportation Infrastructure in Bogor Regency, 2024 - Almyanti Ningrum; Tjahjo Tri Hartono; Immas Nurhayati; Yuggo Afrianto (Universitas Ibn Khaldun Bogor, 2024)
This study evaluates the transportation infrastructure in Bogor Regency by employing a comprehensive Connectivity Index to assess the extent of integration across various transportation modes. The research aims to address pressing challenges, including limited accessibility, inadequate integration, and traffic congestion. Using data on road and rail networks and transportation nodes, three key indicators were analyzed: road-based public transport connectivity, rail-based transport coverage, and the integration of major transportation nodes. Results reveal that road-based connectivity stands at 33.55%, while rail-based connectivity ratio and integrated node percentage are at 0.052 km/km² and 17.02%, respectively. These findings highlight the suboptimal state of intermodal integration in Bogor Regency. The study concludes that targeted investments in rail network expansion and the development of multimodal transportation nodes are imperative. Enhanced integration and connectivity will support sustainable transportation systems, improve mobility, and foster economic development in the region.